Identification of polycyclic aromatic hydrocarbons in sugar cane soot by gas chromatography mass spectrometry - Zamperlini, GCM; Silva, MRS; Vilegas, Wagner [UNESP] (Vieweg, 1997)
Fly soot samples collected in the sugar cane fields after the process of burning were extracted in a Soxhlet apparatus (methylene chloride:methanol 4:1). The extracts were fractionated on silica gel Sep-Pak cartridges into three fractions. A gas chromatographic-mass spectrometric study of the fly soot extracts allowed the identification of the PAH with mutagenic and carcinogenic properties. Large amounts of aliphatic hydrocarbons, fatty acid esters and some PAHs were identified by GCMS in full scan mode. GC-MS in the selective ion monitoring mode (SIM) was suitable for the determination of many PAHs, which are often present in the burnt biomass. 31 PAHs and 7 thiophens derivatives were identified. The presence of these compounds should be regarded as a caution to workers and the general population to avoid exposure to the fly soot.
Keywords: gas chromatography mass spectrometry; sugar cane burning; soot; polycyclic aromatic hydrocarbons